2009
DOI: 10.1016/j.ijpe.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the compliance of a product with an eco-label: From standards to constraints

Abstract: The new awareness of the consumers regarding environmental issues should allow companies to gain a competitive advantage by obtaining eco-labels which certify the low impact of a product on the environment. Getting such label requires to analyse a product according to rules expressed in natural language which may be difficult to interpret but also to apply when the product is complex. In order to address this problem, we suggest a method aiming at providing support to the user when checking the compliance of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 36 publications
0
40
0
3
Order By: Relevance
“…Similarly, Halme et al (2006) and Houe and Grabot (2009) showed that when environmentally friendly products increase buyer perceived quality of life, consumers are more likely to acquire them independently of sex, social class, employment and age group. http://www.ijmp.jor.br v. 4, n. 1, January -June 2013.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
“…Similarly, Halme et al (2006) and Houe and Grabot (2009) showed that when environmentally friendly products increase buyer perceived quality of life, consumers are more likely to acquire them independently of sex, social class, employment and age group. http://www.ijmp.jor.br v. 4, n. 1, January -June 2013.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
“…Companies may seek to communicate their environmental performance to outside stakeholders particularly their customers. To enable dissemination of such information to emission sensitive customers, several authors including Roberts (2008) and Houe and Grabot (2009) have suggested eco-labelling of products.…”
Section: Market Value and Demandmentioning
confidence: 99%
“…These techniques or practices can help control the use of resources during the production process or also in product design (Andriankaja, Vallet, Le Duigou, & Eynard, 2015;Houe & Grabot, 2009;Zhang, Zhan, Liu, Zhang, & Li, 2011;Chiang & Roy, 2012;Fiksel, 2009). Baumann, Boons and Bragd (2002) and Dangelico and Pontrandolfo (2010), seek to integrate environmental aspects into products to minimize the risks of emissions emitted during production, consumption and disposal.…”
Section: Introductionmentioning
confidence: 99%